IMPROVING STUDENTS' SPEAKING SKILL THROUGH SEMANTIC MAPPING A Classroom Action Research of the Tenth Grade Students in SMK Negeri 2 Karanganyar in the Academic Year 2009 / 2010) - SULISTYANTINI, SRI ESTI (2011)
The objective of the research is to find whether semantic mapping can improve students' speaking skill. In this research, the problem refered to the tenth grade students of Machine Program in learning English especially their speaking skill which was still low. Related to the above problem, the writer thought that semantic mapping was the most appropriate one that can be used to increase their motivation and interest to study English especially speaking. The research was a classroom action research. The research methodology included setting and time of the research, the subject of the research, the methods, the procedure of the research, technique of collecting data, and technique of data analysis. The writer divided the action into three cycles and carried out in four steps namely planning the action, implementing the action, observing and monitoring the action, and reflecting and evaluating the result of the action. The result of the implementation showed that the application of semantic mapping improved and enhanced the students' speaking skill. It could be seen from their motivation and interest increased. The obstacles as like passive, low speaking skill and inferior feeling significantly decreased. Besides, from the collected data, the students had better progress from cycle one to the next cycle. For instance, the mean score of pre test was 59.73, while the mean of cycle one was 60.23, cycle two was 69.99, and cycle three was 71.97. Based on the result, it could be concluded that the use of semantic mapping really improved the students' achievement in learning English especially in speaking skill. The improvement was quite significant which was reflected from the progress of the students' score from one cycle to another, besides their increasing motivation and interest. Related to the research findings above, the writer wanted to propose some suggestions for the English teachers. Firstly, learn the characteristics of the students, including the psychological condition and secondly learn how to enhance their ability in teaching English and to establish a good atmosphere in the class.